A glimpse into the genomic outlook of the long-tailed macaque (Macaca fascicularis) - Uli, Joey Ee; Yong, Christina Seok Yien; Tan, Soon Guan (Universiti Putra Malaysia Press, 2017)
The long-tailed macaque (Macaca fascicularis) is commonly used for biomedical researches. However, genetic variation within a population or among populations can significantly affect phenotypical outcomes of treatments tested on model organisms. As such, it is important for studies involving model organisms originating from different, or even the same geographical locations to have sufficient genomic and transcriptomic background of the model organisms that is used. This paper summarises the utilisation of next-generation sequencing (NGS) technology to sequence genomes and transcriptomes of long-tailed macaques from various geographical populations in general and the Malaysian long-tailed macaque in particular, and its importance in the context of population genetic studies.